INOVASI YOUNG COMMUNITY BASED-INITIATIVES DALAM PARIWISATA SURABAYA (RASA MEMILIKI, INOVASI DAN KETERLIBATAN PEMUDA DALAM TURUT MENGEMBANGKAN PARIWISATA SURABAYA) - Nur Emma Suriani (Politeknik Ubaya, 2017)
The aim of this research is to analyze the knowledge of young generations (teenagers) to Surabaya’s tourism. Also, this research investigates how deep their sense of belongings and innovations in developing Surabaya’s tourism. This relates to young people’s understanding about destinations in Surabaya, location, accessibility, as well as history around them. This research examines participation of young generations to tourism development in Surabaya, tourism often ignores the participation of local community. Tourism often only asks the local people to be the spectator. The positive benefits of tourism are often enjoyed by people outside Surabaya. Therefore, this research focuses on the knowledge of local people, particularly the teenagers.